2018
DOI: 10.1107/s205322961801433x
|View full text |Cite
|
Sign up to set email alerts
|

Solvomorphs of tyraminium 5,5-diethylbarbiturate: a rare example of the barbiturateR33(12) hydrogen-bond motif and a crystal structure withZ′ = 4

Abstract: In the past two decades, the solvomorphism phenomenon in organic materials has attracted much attention, especially in the pharmaceutical and materials industries. Cocrystallization with solvent molecules can lead to modified physical and chemical properties of materials. We present here two new solvomorphs (pseudopolymorphs) of tyraminium 5,5-diethylbarbiturate [2-(4-hydroxyphenyl)ethanaminium 5,5-diethyl-2,4,6-trioxotetrahydro-2H-pyrimidin-1-ide, C8H12NO+·C8H11N2O3 −] with unusual structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Hydrate/solvate crystalline compounds (solvomorphs) and their polymorphs have been reported in the pharmaceutical and materials sciences and are responsible for changes in physical and chemical properties (e.g. solubility, melting point, and bioactivity) (Rydz et al, 2018;Barbas et al, 2020). Similar studies of saccharides have been reported in crystals of lactose, cellobiose, and trehalose (Beevers & Hansen, 1971;Nagase et al, 2002;Rencurosi et al, 2002;Listiohadi et al, 2005;Nagase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrate/solvate crystalline compounds (solvomorphs) and their polymorphs have been reported in the pharmaceutical and materials sciences and are responsible for changes in physical and chemical properties (e.g. solubility, melting point, and bioactivity) (Rydz et al, 2018;Barbas et al, 2020). Similar studies of saccharides have been reported in crystals of lactose, cellobiose, and trehalose (Beevers & Hansen, 1971;Nagase et al, 2002;Rencurosi et al, 2002;Listiohadi et al, 2005;Nagase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%